Find the height of the pyramid, wherein
and
, and
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Height is adjacent to right angle. So line A B = t a n 3 0 ∘ h and line A D = t a n 2 8 ∘ h . Using Pythagorean theorem on the base triangle,
( t a n 2 8 ∘ h ) 2 = ( t a n 3 0 ∘ h ) 2 + 1 5 0 2 ( t a n 2 2 8 ∘ h 2 ) = ( t a n 2 3 0 ∘ h 2 ) + 1 5 0 2 h 2 t a n 2 3 0 ∘ = h 2 t a n 2 2 8 ∘ + 1 5 0 t a n 2 3 0 ∘ t a n 2 2 8 ∘ ( t a n 2 3 0 ∘ − t a n 2 2 8 ∘ ) ( h 2 ) = 1 5 0 t a n 2 3 0 ∘ t a n 2 2 8 ∘ h 2 = t a n 2 3 0 ∘ − t a n 2 2 8 ∘ 1 5 0 t a n 2 3 0 ∘ t a n 2 2 8 ∘ h = t a n 2 3 0 ∘ − t a n 2 2 8 ∘ 1 5 0 t a n 2 3 0 ∘ t a n 2 2 8 ∘ h = 2 0 4 . 6 7